First-principles study on the effect of high In doping on the conductivity of ZnO - 侯清玉 李继军 迎春 赵春旺 赵二俊 张跃 (Chinese physics B, 2013)
Based on the density functional theory （DFT）, using first-principles plane-wave ultrasoft pseudopotential method, the models of the unit cell of pure ZnO and two highly In-doped supercells of Zn0.9375In0.0625O and Zn0.875In0.125O are constructed, and the geometry optimizations of the three models are carried out. The total density of states （DOS） and the band structures （BS） are also calculated. The calculation results show that in the range of high doping concentration, when the doping concentration is hihger than a specific value, the conductivity decreases with the increase of the doping concentration of In in ZnO, which is in consistence with the change trend of the experimental results.